Analisis Faktor yang Mempengaruhi Minat Kunjungan Ulang Poli Obstetric dan Gynecology Rumah Sakit Wulan Windi Medan Tahun 2025 - Murni Suryanthi; Denni H. Situmorang; Tatin Wahyanto; Ibnu Jafar; Sondang Sidabutar; Hermawati Purba (Lembaga Pengembangan Kinerja Dosen, 2025)
Hospital health services comprise the whole procedure from patient registration to discharge after medical evaluation or treatment. The execution of high-quality service is essential for hospital success and patient happiness. Service quality may be assessed using the RATER dimensions (Parasuraman et al., 1985). This research seeks to examine the determinants affecting patients' desire to return to the Obstetrics and Gynecology Clinic at Wulan Windi Hospital, Medan, in 2025. The study used a quantitative methodology with a cross-sectional design. The sample included 60 patients from the Obstetrics and Gynecology Clinic, using complete sampling methodology. The findings demonstrated a substantial correlation between the performance of administrative personnel and patients' desire to return (p = 0.003 < 0.05). Additional characteristics, such as facilities, information, accessibility, physician services, and nursing services, were also identified as influencing the propensity to return. The primary determinant influencing patients' desire to return was nurse care, shown by a p-value of 0.001 and an Exp(B)/OR value of 36.026. The data indicate that the quality of nurses' contact, attentiveness, and care significantly influences patient satisfaction and their propensity to return to the Obstetrics and Gynecology Clinic at Wulan Windi Hospital, Medan.